The Effect of the Reciprocal Teaching Learning Model Assisted by Interactive Diagram Media on Collaboration Skills and Cognitive Learning Outcomes of Grade X Students in Biogeochemistry Material - Kennis Rozana; Faiq Aqiilah Arsyaputri (BIO-EDU: Jurnal Pendidikan Biologi, 2026)
The low levels of collaborative skills and inadequate cognitive learning achievement among students in the complex topic of biogeochemistry have motivated this study. A preliminary investigation at SMAN 1 Mojosari revealed that 26 out of 36 students failed to meet the Minimum Competency Standard, and their collaborative skills were rated as only moderate on two key indicators: productive teamwork (57.1%) and showing respect (58.3%). This research aimed to evaluate the effectiveness of the reciprocal teaching model enhanced with interactive diagram media in improving students’ collaboration abilities and enhancing cognitive learning outcomes. A quasi-experimental design with a nonequivalent pretest-posttest control group was employed. Two classes of grade X students (36 students per class) were selected using purposive sampling. Data were collected using cognitive tests and collaboration questionnaires, then analyzed using ANOVA. The findings indicate that the intervention did not significantly influence students’ collaborative skills (p = 0.345 > 0.05), although it significantly improved cognitive learning outcomes (p = 0.000 < 0.05). These results suggest that the reciprocal teaching model, combined with interactive diagram media, effectively enhances cognitive achievement and shows potential for fostering improvements in collaborative skills over time. The effectiveness of this approach is influenced by several factors, including students’ initial ability, limited implementation time, and students’ ability to adapt to the new learning model.